PERAN OSIS DALAM MEMBANGUN KARAKTER KEPEMIMPINAN SISWA MAN 1 NGAWI: 10.56997/inisiasi.v4i2.1997 - syukur, ukasyah abdurrafi; Tyas, Zuhriana Widya Rahayu Ning; Putra, Ricky Setiawan Pariszha Dharma (Institut Agama Islam Ngawi, 2025)
Education, besides being a means of imparting knowledge, also serves as an education that emphasizes character development through OSIS (Student Organization Intra School) leadership skills. At MAN 1 NGAWI, OSIS plays an important role in supporting the formation of student character through school programs and activities. Therefore, this research needs to be conducted to further examine the role of OSIS in building student leadership character and the challenges faced by OSIS in training student leadership. This research uses qualitative methodology, which includes field observation techniques on students of MAN 1 NGAWI. The results of this study indicate that the student council helps in enhancing student leadership through organizational activities, as well as teaching a sense of responsibility, discipline, and initiative in managing work programs, and improving communication and decision-making within the group.